2018
DOI: 10.1002/adma.201706083
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Solar Cells with 90% External Quantum Efficiency Featuring an Ideal Light‐ and Charge‐Manipulation Layer

Abstract: Rapid progress in the power conversion efficiency (PCE) of polymer solar cells (PSEs) is beneficial from the factors that match the irradiated solar spectrum, maximize incident light absorption, and reduce photogenerated charge recombination. To optimize the device efficiency, a nanopatterned ZnO:Al O composite film is presented as an efficient light- and charge-manipulation layer (LCML). The Al O shells on the ZnO nanoparticles offer the passivation effect that allows optimal electron collection by suppressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 51 publications
0
40
0
Order By: Relevance
“…Polymer semiconductors suffer from low mobilities and short diffusion lengths as compared to other types of semiconductors, which limits the active layer thickness and the light absorption. Therefore, optimizing the structure of an OPV is a promising approach toward enhanced light absorption and carrier collection . For example, it has been shown that by introducing a buffer layer between the active layer and electrodes, it is possible to modify the band alignment and reduce the undesired charge carrier recombination sites .…”
Section: Introductionmentioning
confidence: 99%
“…Polymer semiconductors suffer from low mobilities and short diffusion lengths as compared to other types of semiconductors, which limits the active layer thickness and the light absorption. Therefore, optimizing the structure of an OPV is a promising approach toward enhanced light absorption and carrier collection . For example, it has been shown that by introducing a buffer layer between the active layer and electrodes, it is possible to modify the band alignment and reduce the undesired charge carrier recombination sites .…”
Section: Introductionmentioning
confidence: 99%
“…Beside the optimization in the side chains and the end groups, researchers also try to change the fused ring to investigate the effect of conjugation length on the properties of this kind of acceptors. By decreasing the conjugation length of D part to pentacyclic rings, many SMAs such as IC-1IDT-IC [23], IDIC [23,24] and CO5IC [25], were reported with PCEs of 7.39% (PDBT-T1: IC-1IDT-IC), 11.03% (PTFBDT-BZS: IDIC) and 7.49% (PBDB-T: CO5IC) respectively. Furthermore, IHIC [26] and IHIC1 [27] with hexacyclic middle part achieved PCEs of 9.77% (IHIC with PTB7-Th) and 9.21% (IHIC1 paired with FTAZ).…”
Section: Introductionmentioning
confidence: 99%
“…Precise manipulation of light propagation is highly desired in information technology, high power lasers, sensing, and even in light‐harvesting/optical trapping systems . However, such manipulation is highly challenging.…”
Section: Introductionmentioning
confidence: 99%